2018
DOI: 10.1002/anie.201800197
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid‐β Peptide Induces Prion Protein Amyloid Formation: Evidence for Its Widespread Amyloidogenic Effect

Abstract: Transmissible spongiform encephalopathy is associated with misfolding of prion protein (PrP) into an amyloid β-rich aggregate. Previous studies have indicated that PrP interacts with Alzheimer's disease amyloid-β peptide (Aβ), but it remains elusive how this interaction impacts on the misfolding of PrP. This study presents the first in vitro evidence that Aβ induces PrP-amyloid formation at submicromolar concentrations. Interestingly, systematic mutagenesis of PrP revealed that Aβ requires no specific amino ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…Interestingly, the kinetic profile for p3 F20Y closely matched that of p3, while p3 F19Y exhibited a slightly attenuated onset of aggregation. This may indicate a favorable interaction between F19 and another residue, reinforced by the discovery that a F19P mutation abolishes Aβ aggregation . Moreover, our findings are supported by Bitan et al showing that truncations of residues 1–9 of Aβ do not inhibit oligomer formation .…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Interestingly, the kinetic profile for p3 F20Y closely matched that of p3, while p3 F19Y exhibited a slightly attenuated onset of aggregation. This may indicate a favorable interaction between F19 and another residue, reinforced by the discovery that a F19P mutation abolishes Aβ aggregation . Moreover, our findings are supported by Bitan et al showing that truncations of residues 1–9 of Aβ do not inhibit oligomer formation .…”
supporting
confidence: 86%
“…This may indicate a favorable interaction between F19 and another residue, reinforced by the discovery that a F19P mutation abolishes Aβ aggregation. 54 Moreover, our findings are supported by Bitan et al showing that truncations of residues 1−9 of Aβ do not inhibit oligomer formation. 49 Aβ also formed similar assembly sizes in addition to faint signals corresponding to high-N structures (20−30 kDa).…”
supporting
confidence: 85%
“…According to the amyloid cascade hypothesis, promoting the clearance of amyloid or reducing its aggregation has been the goals of preclinical and clinical studies for several decades (Mullard, 2016 ). Recently, numerous studies found that amyloid pathology can spread in the AD brain like prions (Honda, 2018 ; McAllister et al, 2020 ). This is not inconsistent with senile plaques influencing the brain microenvironment and facilitating more amyloid‐β production, aggregation and spreading.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that previously reported cases analyzed the interaction of amyloid proteins that had the ability of coming into contact in vivo (alpha-synuclein, Tau, prion proteins, and amyloid-beta) [24,[28][29][30][31][32], it was interesting to examine if such amyloid crossinteractions can occur between proteins that do not share a localization. From these results, it is clear that the presence of lysozyme fibrils has a major impact on the aggregation mechanism of insulin.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies displaying heterogenous cross-interactions of neurodegenerative disease-related amyloid proteins. It was shown that amyloid-beta aggregates are capable of inducing/enhancing the fibrilization of non-aggregated alpha-synuclein [24], Tau [28], and prion proteins [29]. Similarly, alpha-synuclein aggregates had a positive effect on Tau [30] and prion protein fibrilization [31].…”
Section: Introductionmentioning
confidence: 99%